POTENSI GEOWISATA DAERAH KECAMATAN RATATOTOK DAN SEKITARNYA MELALUI ANALISIS GEOSITE DAN GEOMORPHOSITE - Momongan, Andrew (LPPM Universitas PRISMA, 2023)
The Ratatotok area and its surroundings have attractive geotourism potential which includes plains and coastal elements. Morphologically, this area has varied landscapes ranging from lava flowing hills, karst hills, alluvial plains, headlands and bays, geological structure control areas to coral reef exposure in shallow seas. Researchers assessed the feasibility of development using the initial approach of geosite and geomorphosite analysis. Five geosite and geomorphosite locations were found in the study area including Tanjung Mangkit, Gamping Ratatotok Cave, Megawati Soekarno Putri Botanical Garden area, Tanjung Buyat–Lakban, and Lake Buyat. The feasibility assessment results show the value of the five geotourism prospect locations sequentially, namely 59.5%, 50%, 70.3%, 60% and 58%. From the research results, the reclamation area for the Megawati Soekarno Putri Botanical Garden is very feasible to be developed into a geotourism object, as well as Tanjung Buyat–Lakban which is categorized as feasible for development, while the other three locations still need to develop main and supporting infrastructure. The development of an integrated geotourism area can help develop geotourism potential and increase people's welfare through the ecotourism sector.